La femme idealisée et la condition de la femme dans l’œuvre de Panaït Istrati - Stefania GORZO (Diversitate si Identitate Culturala in Europa)
This article examines the way women are portrayed by Panaït Istrati, a Romanian writer of French expression. Through his unique, unconventional female characters, Istrati criticizes the social norms built for women by an unjust patriarchal system. The “haïdouck” woman (outlaw) represents his ideal woman, a prototype that tends towards autonomy and emphasizes the central values of the author: freedom, compassion, justice. Istrati’s female characters stand out for their courage and fighting spirit.